Potensi Ketahanan Pangan sebagai Perekonomian Desa Sababilah dalam Mendukung Ketersediaan Pangan Kabupaten Barito Selatan - Reki Saparudin; Mega Maharani; Yuni Christina BR Sembiring; Rosaria Imelda; Bertha Hotmaida Nainggolan; Desi Ratna Sri Dewi; Suriyantie Suriyantie; Risma Viola; Yahya Josia; Satria Mandala Putra; Mangka Dilaga; Indra Oka Framana; Deby Silaban; Wita Amelia Natalia; Yulintine Yulintine (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Sababilah Village in Dusun Selatan District, South Barito Regency, has great potential to increase food security through optimal resource management. With lowland topography and a tropical climate, this village has fertile soil that is ideal for various plants. The 2024 Real Work Lecture Program (KKN-T) from Palangka Raya University focuses on developing food security by planting various plants using innovative planting media containers such as drinking water glasses and providing technical assistance in watermelon harvesting. The results of the activity show that this agricultural technique is effective in utilizing local resources and increasing crop yields. To increase success, it is recommended that villages expand modern agricultural training, involve communities more actively, and develop local markets for agricultural products. Regular evaluation is also important to ensure the program's sustainability and positive impact.